Epidemiologic Profile of Seborrheic Keratosis and Acrochordon at the National Referral Hospital in Indonesia - Purbasari, Lusiana; Larasati, Anindya; Paramitha Wibawa, Larisa (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Seborrheic keratosis (SK) and acrochordon are common benign neoplasms of the skin thatan be diagnosed clinically. Management of SK and acrochordon has a wide range of purposes, including aesthetic appearance and health concerns. Epidemiologic data for these entities is rare in Indonesia. Purpose: To determine the epidemiology of SK and acrochordon patients at the Dermatology & Venereology (DV) Clinic, dr. Cipto Mangunkusumo National Central General Hospital (RSCM). Method: Patient registry data at the DV Clinic, RSCM from 2014 to 2017 was collected retrospectively. Data was obtained by using the total sampling method and retrieving characteristics such as age, sex, and outpatient-based procedures. Result: In the four-year period, there were 1.202 SK patient visits with 447 new cases and 374 acrochordon patient visits with 169 new cases. The proportion of SK patients in this study was 2.2%; acrochordon was 1.8% of all patients at the DV Clinic of RSCM. The highest prevalence of SK was found in patients older than the 6th decade, while for acrochordon, it was within the 4th decade. Both SK and acrochordon were seen higher in women, with a male-to-female ratio of 1:2. Electrosurgery was the most common office procedure performed. Conclusion: Seborrheic keratosis and acrochordon proportion, respectively, are 2.2% and 1.8% at the DV Clinic, RSCM. Seborrheic keratosis and acrochordon are more frequent in women, with the peak occurring in 6th decade and 4th decade, respectively